A state parameter-based scaling law for centrifuge modelling. Issue 162 (November 2022) - Ma, Qiang; Zhou, Yan-Guo; Yang, Xiao-Tian; Chen, Yun-Min
Abstract: When centrifuge modelling is applied to a prototype with large geometries that the centrifugal acceleration ( Ng ) could not fully recover the overburden stress of the prototype in the model, the generalized scaling law proposed by Iai (i.e., Iai's GSL) is often a promising choice. However, the scaling factor of shear strain is always larger than unity in Iai's GSL, which leads to the fact that the strain of the model soil is always smaller than that of the prototype. To address such a problem in Iai's GSL, a state parameter-based centrifuge scaling law securing the same shear strain between the model and the prototype is proposed in this paper. The proposed scaling law controls the model and the prototype to have the same initial state parameter by adjusting the void ratio of the model. The corresponding depth variation of the initial void ratio of the model is derived theoretically. To simplify the procedure of controlling the continuous change of void ratio through the model depth, a simplified approach is adopted for model preparation. The resultant effects of the proposed scaling law on soil density and permeability coefficient for different types of soils are also discussed. Finally, three centrifuge model tests of a submerged gently sloping ground of Ottawa F-65 sand with the same target geometry, state parameter and input motion at prototype scale have been conducted to validate the proposed scaling law, where the dynamic response and liquefaction-induced deformations were carefully monitored and analyzed. The applicability of the proposed scaling law is well confirmed by the centrifuge model test results. Highlights: A state parameterbased scaling law is proposed to model the dynamic response of liquefiable ground in centrifuge. The void ratio of model is derived theoretically and the effects on soil density and permeability are discussed. Model preparation method is proposed to secure the same state parameter between the model and the prototype. The proposed scaling law is validated by technique of "modelling of models" in centrifuge model tests.